PEMBINAAN BACAAN AL-QUR’AN MELALUI METODE AT-TANZIL DI TAMAN PENDIDIKAN AL-QUR’AN BAITUL QUR’AN PROBOLINGGO - Lisun Ibnu Fajar; M. Jadid Khadavi (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2023)
Every Muslim around the world received an order from Allah SWT to make the Qur'an a guide to life. To understand the Qur'an requires a real effort, namely reading, worrying, and practicing it in everyday life. Muslims have a very big responsibility to learn and at the same time prohibit other people from reading the Qur'an. Reading the Koran properly and correctly is part of an effort to use the Koran as a guide for life in order to gain inner peace. Several Al-Qur'an educational institutions have tried various methods of reading the Qur'an. However, in this case, the author feels the need to conduct research on the development of Al-Qur'an reading through the At-Tanzil method in the Baitul Qur'an Education Park, Probolinggo. This method is felt to be able to have a concrete positive impact on the students in terms of reading the Koran. The At-Tanzil method at TPQ Baitul Qur'an Karanganyar Probolinggo has succeeded in improving the quality of the students' reading of the Koran based on the science of recitation. By reading the Qur'an properly and correctly, the students are expected to be able to increase their motivation to learn the Qur'an, which does not only stop at aspects of reading but can understand the meaning of the Qur'an more broadly.